Pengaruh model pembelajaran challenge based learning dan problem based learning terhadap literasi numerasi ditinjau dari self efficacy peserta didik kelas 5 sekolah dasar - Harnanda Mita Anggar Sari; Sri Marmoah; Tri Budiharto (Universitas Sebelas Maret, 2025)
This research aims for analyze the Challenge Based Learning (CBL) and Problem Based Learning (PBL) learning models in numeracy abilities of grade 5 students at Sondakan State Elementary School, Surakarta, in terms of the level of self-ability. The subjects of this research were 49 grade 5 students consisting of 25 control class and 24 experimental class students. The research approach used was quasi-experimental with a non-equivalent control group design. The research sample consisted of two classes selected using purposive sampling, where one class applied the CBL model and the other class applied the PBL model. Research instruments include numeracy tests and self-efficacy questionnaires. Data analysis was carried out using the t-test to determine the average difference in numeracy ability between the two groups. The results of the study showed that there was a significant difference in increasing numeracy skills between the groups who studied with the CBL and PBL models. Apart from that, students' self-efficacy is also proven to have a significant influence on their numeracy abilities. Students with high levels of self-efficacy show better numeracy improvements compared to students with low levels of self-efficiency, both in CBL and PBL learning models. Kata kunci: numeracy, learning models, self efficacy